Yang-xin-xue keli exerts therapeutic effects via regulating mitochondrial homeostasis and function in doxorubicin-induced rat heart failure - Long, Kunlan; Zhao, Ziyi; Chen, Jun; Zhi, Lijia; Wang, Chunxia; Liao, Dan; Wang, Meng; Gao, Peiyang (Frontiers in Pharmacology, 2022)
Background: Heart failure, especially chronic heart failure, is generally induced by the accumulation of reactive oxygen species (ROS), as well as the subsequent loss of mitochondrial permeability transition pore (mPTP) openings and pathological mitochondrial dysfunction. Herein, we explored the therapeutic effects of the Chinese medicine Yangxin Keli (YXXKL) on chronic heart failure and its underlying working mechanism. Methods: To mimic oxidative stress-induced chronic heart failure, a rat heart failure model was induced by the administration of DOX. Transthoracic echocardiography was performed to confirm the successful establishment of the heart failure model by observing significantly decreased cardiac function in the rats. Mitochondrial membrane potential, function, and ATP synthesis activity were measured after YXXKL was employed. Results The administration of YXXKL not only significantly improved cardiac function but also reversed the myocardium loss and fibrosis induced via DOX. Moreover, the administration of YXXKL also increased ATP synthesis and mitochondrial DNA mass in left ventricular tissues, which indicated that mitochondria may be a key target of YXXKL. Thus, we employed rat cardiomyocyte H9c2 and primary rat cardiac myocytes (RCMs) to induce oxidative stress-induced myocardial injury via DOX treatment. YXXKL-medicated serum promoted cell proliferation, which was inhibited by the addition of IC30 DOX, and the serum also inhibited cell apoptosis, which was promoted by the addition of IC50 DOX. YXKL-medicated serum was able to scavenge ROS and maintain the mitochondrial membrane potential as well as promote mitochondrial function, including the promotion of ATP synthesis, mitochondrial DNA mass, and transcriptional activity. Furthermore, we also observed that YXXKL-medicated serum inhibited DOX-induced autophagy/mitophagy by scavenging ROS. Conclusion: Taken together, we conclude that YXXKLI may exert therapeutic effects on oxidative stress-related heart failure via the regulation of mitochondria.